2015
DOI: 10.1371/journal.pone.0139910
|View full text |Cite
|
Sign up to set email alerts
|

Kefir Grains Change Fatty Acid Profile of Milk during Fermentation and Storage

Abstract: Several studies have reported that lactic acid bacteria may increase the production of free fatty acids by lipolysis of milk fat, though no studies have been found in the literature showing the effect of kefir grains on the composition of fatty acids in milk. In this study the influence of kefir grains from different origins [Rio de Janeiro (AR), Viçosa (AV) e Lavras (AD)], different time of storage, and different fat content on the fatty acid content of cow milk after fermentation was investigated. Fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 57 publications
5
24
2
2
Order By: Relevance
“…e different behaviour of citric acid levels in cow's milk and soy milk kefir (Table 4) indicated that the microbiota can influence the organic acid balance resulting in organoleptic and antimicrobial characteristics of kefirs [2,13]. Similar results for organic acid content have been reported for cow's milk kefir [13,25,26] and soy milk kefir [27,28]. e total free amino acid concentration for cow's milk kefir differs between the reports.…”
Section: Discussionmentioning
confidence: 54%
“…e different behaviour of citric acid levels in cow's milk and soy milk kefir (Table 4) indicated that the microbiota can influence the organic acid balance resulting in organoleptic and antimicrobial characteristics of kefirs [2,13]. Similar results for organic acid content have been reported for cow's milk kefir [13,25,26] and soy milk kefir [27,28]. e total free amino acid concentration for cow's milk kefir differs between the reports.…”
Section: Discussionmentioning
confidence: 54%
“…According to Vieira et al. (), higher oleic acid and MUFA were determined to fermented kefir, whereas lower SFA contents were found. They also displayed increase in PUFA after fermentation.…”
Section: Discussionmentioning
confidence: 94%
“…The aforementioned kefir grains are microbially derived protein and polysaccharide matrices that contain a community of bacterial and fungal species that are essential to kefir fermentation [ 260 ]. When fermenting, lactic acid, bioactive peptides, exopolysaccharides, antibiotics and bacteriocins are produced [ 225 , 261 ] and the fatty acid composition is altered [ 262 ]. The microorganisms in kefir have probiotic potential and may have a positive impact on gut health.…”
Section: Functional Alternative Dairy Foods and Consumer Trendsmentioning
confidence: 99%